Comparison of Endoscopic Endonasal Approach and Lateral Microsurgical Infratemporal Fossa Approach to the Jugular Foramen: An Anatomical Study - Liu, Jianfeng; Pinheiro-Neto, Carlos D.; Yang, Dazhang; Wang, Eric; Gardner, Paul A.; Hirsch, Barry E.; Snyderman, Carl H.; Fernandez-Miranda, Juan C. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The jugular foramen is one of the most challenging surgical regions in skull base surgery. With the development of endoscopic techniques, the endoscopic endonasal approach (EEA) has been undertaken to treat some lesions in this area independently or combined with open approaches. The purpose of the current study is to describe the anatomical steps and landmarks for the EEA to the jugular foramen and to compare it with the degree of exposure obtained with the lateral infratemporal fossa approach.Materials and Methods A total of 15 osseous structures related to the jugular foramen were measured in 33 adult dry skulls. Three silicone-injected adult cadaveric heads (six sides) were dissected for EEA and three heads (six sides) were used for a lateral infratemporal fossa approach (Fisch type A). The jugular foramen was exposed, relevant landmarks were demonstrated, and the distances between relevant landmarks and the jugular foramen were obtained. High-quality pictures were obtained.Results The jugular foramen was accessed in all dissections by using either approach. Important anatomical landmarks for EEA include internal carotid artery (ICA), petroclival fissure, inferior petrosal sinus, jugular tubercle, and hypoglossal canal. The EEA exposed the anterior and medial parts of the jugular foramen, while the lateral infratemporal fossa approach (Fisch type A) exposed the lateral and posterior parts of the jugular foramen. With EEA, dissection and transposition of the facial nerve was avoided, but the upper parapharyngeal and paraclival ICA may need to be mobilized to adequately expose the jugular foramen.Conclusion The EEA to the jugular foramen is anatomically feasible but requires mobilization of the ICA to provide access to the anterior and medial aspects of the jugular foramen. The lateral infratemporal approach requires facial nerve transposition to provide access to the lateral and posterior parts of the jugular foramen. A deep understanding of the complex anatomy of this region is paramount for safe and effective surgery of the jugular foramen. Both techniques may be complementary considering the different regions of the jugular foramen accessed with each approach.
Keywords: jugular foramen; internal carotid artery; infratemporal fossa; endoscopic; endonasal; microscopic; skull base surgery